Educational leadership as action: Towards an opening of rhythm - Waghid, Y; Davids, N (South African Journal of Higher Education, 2016)
Nowadays, its seems as if higher education institutions have unobtrusively adopted leadership styles that seem to be in consonance with neoliberal, managerialist approaches to leadership in education. It has become apparent that, to lead, one has to occupy particular authoritative positions. Yet following such an account of leadership, institutional practices become more attuned to leadership styles in which it is erroneously assumed that people need to be told what to do and how they need to do it in order to meet the demands of the neoliberal and managerialism associated with the attainment of high levels of productivity within the institutions. Unfortunately, as we shall argue, such leadership approaches militate against the very idea of education and its intertwined practices. Consequently, we advocate a position of leadership in education that enhances the doing of action that opens up that to which Agamben (1999) refers to as ‘rhythm’. Education, we argue, has a better chance of being realised and sustained if institutions attune their practices towards an opening of rhythm – one that departs from an instrumentalist, leadership-by-position towards leadership that embraces rhythmic action.